2020
DOI: 10.1088/1475-7516/2020/07/024
|View full text |Cite
|
Sign up to set email alerts
|

The angular resolution of GRAPES-3 EAS array after improved timing and shower front curvature correction based on age and size

Abstract: The angular resolution of an extensive air shower (EAS) array plays a critical role in determining its sensitivity for the detection of point γ-ray sources in the multi-TeV energy range. The GRAPES-3, an EAS array located at Ooty in India (11.4̂N, 76.7̂E, 2200 m altitude) is designed to study γ-rays in the TeV-PeV energy range. It comprises of a dense array of 400 plastic scintillators deployed over an area of 25000 m2 and a large area (560 m2) muon telescope. The development of a new statistical method has al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…This improves to (0.29±0.06) • at >200 TeV with a significance of 3.1σ (Figure 4d). These results are consistent with the earlier analysis [6] described in the previous subsection and comparable with other experiments that are located at almost twice the altitude of GRAPES-3 (Figure 4e). We estimated the pointing accuracy of the EAS array along right ascension (α) and declination (δ) to be (0.032±0.004) • and (0.090±0.003) • , respectively (Figure 4f).…”
Section: Cosmic Ray Shadow Of the Moonsupporting
confidence: 93%
See 2 more Smart Citations
“…This improves to (0.29±0.06) • at >200 TeV with a significance of 3.1σ (Figure 4d). These results are consistent with the earlier analysis [6] described in the previous subsection and comparable with other experiments that are located at almost twice the altitude of GRAPES-3 (Figure 4e). We estimated the pointing accuracy of the EAS array along right ascension (α) and declination (δ) to be (0.032±0.004) • and (0.090±0.003) • , respectively (Figure 4f).…”
Section: Cosmic Ray Shadow Of the Moonsupporting
confidence: 93%
“…Conventionally it has been corrected by applying a constant curvature (0.215 ns•m −1 ) to the shower front, and then a planar fit is performed to estimate the EAS direction. In a recent study, it was found that the shower front curvature has a strong dependence on shower size and shower age [6]. In this work, the curvature dependences were studied in great detail and corrected to get an improved fit.…”
Section: Improvements In Angular Resolutionmentioning
confidence: 98%
See 1 more Smart Citation
“…The EAS parameters such as core location, size, and age were obtained by fitting a Nishimura-Kamata-Greisen (NKG) function to the lateral distribution of particle densities (Kamata & Nishimura 1958;Greisen 1960). The directions of individual EASs in terms of zenith and azimuth angles (θ, f) were obtained by a fitting a plane front to the relative arrival time data recorded on each scintillator detector after correcting for the curvature in the shower front, which is observed to be dependent on both size and age parameters (Jhansi et al 2020;Pattanaik et al 2022). About 20% of the EAS events, mainly of low energies, could not be reconstructed properly by the NKG function.…”
Section: The Grapes-3 Experiments and Data Setmentioning
confidence: 99%
“…While an initial estimate of the direction of the EAS is obtained by fitting a plane to the observed arrival times in different scintillator detectors, a more accurate estimation of direction is obtained after correcting the shower front curvature based on 𝑁 𝑒 and 𝑠 [32].…”
Section: Reconstruction Of Easmentioning
confidence: 99%